2021
DOI: 10.3390/ijms22094849
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Silver Nanoparticles in Overcoming the Intrinsic Resistance of Pseudomonas aeruginosa to Secondary Metabolites from Carnivorous Plants

Abstract: Carnivorous plants are exemplary natural sources of secondary metabolites with biological activity. However, the therapeutic antimicrobial potential of these compounds is limited due to intrinsic resistance of selected bacterial pathogens, among which Pseudomonas aeruginosa represents an extreme example. The objective of the study was to overcome the intrinsic resistance of P. aeruginosa by combining silver nanoparticles (AgNPs) with secondary metabolites from selected carnivorous plant species. We employed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Synergistic interactions with AgNPs increased the efficacy of reduced 3ChPL concentrations, at which they are non-toxic to human keratinocytes (Krychowiak et al, 2018). Further studies have shown that AgNPs overcome intrinsic microbial resistance to NQs (Krychowiak-Maśnicka et al, 2021). 3ChPL also has high activity toward cancer cells, particularly breast cancer cells (IC 50 = 0.6-2 μM).…”
Section: Naphthoquinones In Various In Vitro Drosera and Dionaea Plan...mentioning
confidence: 99%
“…Synergistic interactions with AgNPs increased the efficacy of reduced 3ChPL concentrations, at which they are non-toxic to human keratinocytes (Krychowiak et al, 2018). Further studies have shown that AgNPs overcome intrinsic microbial resistance to NQs (Krychowiak-Maśnicka et al, 2021). 3ChPL also has high activity toward cancer cells, particularly breast cancer cells (IC 50 = 0.6-2 μM).…”
Section: Naphthoquinones In Various In Vitro Drosera and Dionaea Plan...mentioning
confidence: 99%
“…The rapid increase in the number of drug-resistant P. aeruginosa isolates in clinical settings poses a severe therapeutic challenge and has resulted in a higher mortality rate among patients with the infection ( 1 ). P. aeruginosa is characterized by intrinsic resistance to a broad range of antimicrobial drugs ( 2 , 3 ). Biofilm-producing P. aeruginosa is the reason for a wide variety of serious infections such as post-surgical infections, otitis media, periodontitis, thermal burns, trauma, and cystic fibrosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%